Morphological Changes and Immunohistochemical Expression of RAGE and its Ligands in the Sciatic Nerve of Hyperglycemic Pig (Sus Scrofa) - Juranek, Judyta K. (2010)
The aim of our project was to study the effect of streptozotocin (STZ)—induced hyperglycemia on sciatic nerve morphology, blood plasma markers and immunohistochemical expression of RAGE (the Receptor for Advanced Glycation End-products), and its ligands—S100B and Carboxymethyl Lysine (CML)-advanced glycation endproduct (AGE) in the laboratory pig. Six months after STZ—injections, blood plasma measurements, morphometric analysis of sciatic nerve fiber density, immunofluorescent distribution of potential molecular neuropathy contributors, ELISA measurement of plasma AGE level and HPLC analysis of sciatic nerve levels of one of the pre-AGE and the glycolysis intermediate products—methyl-glyoxal (MG) were performed. The results of our study revealed that STZ—injected animals displayed elevated levels of plasma glucose, gamma glutamyl transferase (GGT) and triglycerides. The sciatic nerve of STZ-injected pigs revealed significantly lower numbers of small-diameter myelinated fibers, higher immunoreactivity for RAGE and S100B and increased levels of MG as compared to control animals. Our results correspond to clinical findings in human patients with hyperglycemia/diabetes-evoked peripheral neuropathy and suggest that the domestic pig may be a suitable large animal model for the study of mechanisms underlying hyperglycemia-induced neurological complications in the peripheral nerve and may serve as a relevant model for the pre-clinical assessment of candidate drugs in neuropathy.